Analiza kosztów przedsiębiorstwa na przykładzie F.H.U. "MIŚ" S.C. w Tarnowie - Błoniarczyk, Ewelina (My University, 2014)
Tematem pracy jest: Analiza kosztów przedsiębiorstwa na przykładzie F.H.U. „MIŚ” S.C. w Tarnowie. Praca składa się z trzech rozdziałów. Rozdział pierwszy zawiera pojęcie kosztów oraz ich klasyfikację. W rozdziale drugim przedstawiono rachunek kosztów w przedsiębiorstwie, ewidencję oraz dokumentację związaną z ewidencjonowaniem i rozliczaniem kosztów. Rozdział trzeci zawiera prezentacje i analizę badań własnych opartych na przedsiębiorstwie F.H.U. „MIŚ” S.C. w Tarnowie.

The theme of the work is: Cost analysis of the company as exemplified by F.H.U. "MIŚ" S.C. in Tarnow. Work consists of three chapters. The first chapter contains term costs and their classification. In the second chapter presents cost accounting in the enterprise, records and documentation related to the recording of and accounting costs. The third section contains presentation and analysis of research based own company F.H.U. "MIS" S.C. in Tarnow.
Cost analysis of the company as exemplified by F.H.U. "MIŚ" in Tarnow
Keywords: rachunek kosztów; rachunkowość finansowa; koszty; analiza; bill of costs; financial accounting; costs; analysis